(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
The present investigation was carried out to determine the possible bioactive compounds of ethanolic extract of Elaeocarpus serratus (Elaeocarpaceae) has been subjected to GC-MS analysis. Thirty compounds were detected from the plant E. serratus. The highest peak area percentage of 19.12% was obtained by n-propanol (RT=3.04min.) and lowest peak area percentage of 2.34% was obtained by 1-propylthio-3,3,3-trifluoropropyl acetate (RT=11.57min.). The presence of various bioactive compounds confirms many aliments by traditional practitioners. However, isolation of individual phytochemical constituents may proceed to find a novel drug.